2020
DOI: 10.1177/2054358120910329
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Use in Patients With Advanced Chronic Kidney Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Pain is common in patients with chronic kidney disease (CKD). Analgesics may be appropriate for some CKD patients. Objectives: To determine the prevalence of overall analgesic use and the use of different types of analgesics including acetaminophen, nonsteroidal anti-inflammatory drugs (NSAIDs), adjuvants, and opioids in patients with CKD. Design: Systematic review and meta-analysis. Setting: Interventional and observational studies presenting data from 2000 or later. Exclusion criteria included ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…Despite guideline recommendations to avoid NSAIDs in kidney transplant recipients whenever possible, and to limit to specific acute pain syndromes such as gout, we found that 11% of recipients were prescribed an NSAID. This is less than the pooled prevalence of 17% in a recent systematic review of patients with chronic kidney disease categories G3-5, 33 but double the frequency of NSAID prescriptions (5%) in kidney transplant recipients reported by Chiasson et al 6 As our study could not capture over-the-counter NSAIDs, it is surprising that the frequency of NSAID prescriptions was higher in our study compared to that of Chiasson et al which captured over-the-counter NSAIDs through a comprehensive Veterans Affairs medical record system. In addition, NSAID prescriptions among kidney transplant recipients in our study was substantially higher than that observed in a U.S. study of living kidney donors, another population in whom risk of kidney-related complications is of concern due to solitary functioning kidney.…”
Section: Discussionmentioning
confidence: 64%
“…Despite guideline recommendations to avoid NSAIDs in kidney transplant recipients whenever possible, and to limit to specific acute pain syndromes such as gout, we found that 11% of recipients were prescribed an NSAID. This is less than the pooled prevalence of 17% in a recent systematic review of patients with chronic kidney disease categories G3-5, 33 but double the frequency of NSAID prescriptions (5%) in kidney transplant recipients reported by Chiasson et al 6 As our study could not capture over-the-counter NSAIDs, it is surprising that the frequency of NSAID prescriptions was higher in our study compared to that of Chiasson et al which captured over-the-counter NSAIDs through a comprehensive Veterans Affairs medical record system. In addition, NSAID prescriptions among kidney transplant recipients in our study was substantially higher than that observed in a U.S. study of living kidney donors, another population in whom risk of kidney-related complications is of concern due to solitary functioning kidney.…”
Section: Discussionmentioning
confidence: 64%
“…Our findings, while not directly comparable, are population-based and may reflect differences in health systems and access to care. A recent systematic review and meta-analysis 11 of patients with GFR category CKD G3-5 CKD reported a point prevalence of 17% for NSAID use. This review also reported an increase in NSAID use in more recent studies and speculated that this may reflect the desire of care providers to avoid opioids for pain management.…”
Section: Discussionmentioning
confidence: 99%
“…10 At present, reports on NSAID use in CKD are heterogeneous, often relying on self-report data and from older studies. 11 Furthermore, previous studies have largely been limited to the elderly population and to those with kidney failure and/or on dialysis. 9 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe hypoglycemic encephalopathy in a patient with CKD, masked by hyperuricemia, has been described [ 62 ]. Pain is common in patients with neuropathy and osteoarthritis and is preferentially treated with acetaminophen in patients with CKD [ 63 ]. Glucose dehydrogenase monitors are not affected by uric acid and acetaminophen but provide falsely high glucose readings in patients treated with icodextrin containing peritoneal dialysis solutions [ 64 ].…”
Section: Main Textmentioning
confidence: 99%